Cost Threshold Approach of Network Association in 5G Non-Standalone System - Widiarti, Helena (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2021)
5G as the latest generation of wireless communication has been an interesting research topic, with a promise to provide a higher data rate and lower latency to user. 5G uses mmWave band to transmit and receive data. Thus, 5G transmission band resides in different band compared to LTE Macrocell. The mmWave has been utilized due to its ability to provide larger bandwidth to user. In spite of the merit, mmWave also brings challenges. The cell range of mmWave is smaller than previous 3G/4G macro cell. Furthermore, the mmWave channels may not reliable, thus it would be preferable to have microwave band as a carrier used to send important control signaling to user. In this case, it should be connected to two network, the main and the secondary network for a user to have a reliable connection. In 3GPP specification, this concept is known as dual connectivity. In this paper, a method based on threshold value for initiating dual connectivity to 5G BS, with LTE BS as the master node and 5G BS as a secondary node has been proposed. The method considered throughput requirement of user, distance to 5G BS and macrocell as criteria for the input parameters to make decision. The algorithm designed to be simple since it will run on the user terminal. Our analysis showed that the proposed method reflects MS distance to 5G AP and load of both LTE Macrocell and 5G AP, in term of cost calculation; thus, it can reduce unnecessary overhead, while at the same time provide user with a required throughput.